Effect of Garcinia Kola on the Reproductive Organ Weight and Histology of the Testis and Anterior Pituitary Gland of Wistar Rats (Journal of Experimental and Clinical Anatomy, 2004)
The effect of Garcinia kola on the reproductive organ weight and histology of the testis and anterior pituitary gland of Wistar rats was investigated. Twenty male Wistar rats weighing on the average 190g body weight, were used in this study and were divided into 4 groups (A,B,C,D) of 5 rats each. Group A rats were used as control and were fed normal rate chow only and water ad libitum. Group B rats were fed Garcinia kola diet (5%w/w). Group C rats were fed with Garcinia kola diet (10% w/w) while group D rats were fed Garcinia kola diet (15% w/w) and both groups had water ad libitum. A significant (p<0.05) fall in body weight and weight of testis was observed there were no significant change in weight of Epididymis, Seminal vesicle, and Ventral prostrate. Histological observation revealed that, group B rats, did not show any structural difference in both testis and anterior pituitary gland, when compared to group A. groups C and D rats however, revealed disruption of basement membrane of seminiferous tubule of testis, near absence of sperm in lumen of seminiferous tubule, increase in interstitial space and reduction in interstitial cells of Leydig. Congestion of cells of anterior pituitary gland were observed, these changes being marked in group D rats. The significance of this study therefore is that Garcinia kola has an inhibitory effect on the reproductive activities of male Wistar rats.